Pain and physical functioning in neuropathic pain: a systematic review of psychometric properties of various outcome measures - Meeta, Poonam; Claydon, Leica S.; Hendrick, Paul; Cook, Chad; Baxter, David G. (Wiley, 2016)
INTRODUCTION: